Toward the elimination of NTDs: application of cost-effective and sensitive molecular environmental surveillance tools—a pilot study - Hodgson, Juliet; Twieku, Gideon; Quarcoo, Gerard; Armah, Emmanuel; Osei-Atweneboana, Mike Yaw; Armoo, Samuel (Frontiers in Parasitology, 2024)
Neglected Tropical Diseases (NTDs) affect over a billion people worldwide. The 2021-2030 NTDs roadmap calls for innovative and highly efficient interventions to end or significantly reduce the burden of NTDs. These include sensitive and cost-effective diagnostic techniques for disease surveillance. Environmental surveillance has been employed effectively in this regard to measure and track infectious diseases such as polio on a population-wide scale. In this study, environmental surveillance was used as a cost-effective tool for detection of soil-transmitted helminths (STHs) in Accra (Ghana), in an area which is populated by urban vegetable farmers. The activities of urban farmers expose them to the risk of STH infection, as well impacting transmission in urban areas, since leafy vegetables may carry infective stages of STHs. A total of 32 wastewater samples were collected from eight points on the Nima Creek (main source of irrigation for the farmers) over a 7-week period. Real-time PCR followed by melt peak analysis were used to screen four STHs (Ascaris lumbricoides, Necator americanus, Ancylostoma duodenale and Trichuris trichiura). Our study revealed A. lumbricoides (17 out of 32 wastewater samples -53.3%) as the most prevalent STH, followed by A. duodenale (31.2%), T. trichiura (21.9%) and N. americanus 12.5%.Environmental surveillance helps to detect the kinds of STH pathogens circulating within the community, and help design mass drug administration (MDA) strategies. This surveillance technique can also provide preliminary information for environmental modifications to help reduce STH transmission in line with the One Health approach recommended by the 2021-2030 NTDs roadmap.